A new species of Cryptoperla Needham, 1909 (Plecoptera: Peltoperlidae) from Guangxi of China, based on male, female, and larval stage - Li, Weihai; Murányi, Dávid (Zootaxa, 2018)
Cryptoperla teana sp. n. is described from male and female adults, larvae, and exuviae collected on the plateau of the Daming Mountains, Guangxi Zhuang Autonomous Region, of southern China. The present discovery represents the first record of the family Peltoperlidae in Guangxi. The distribution of its congeners is illustrated on a map.